2002
DOI: 10.1108/09513570210418888
|View full text |Cite
|
Sign up to set email alerts
|

Professionalism, organizational‐professional conflict and work outcomes

Abstract: This study examines the relationships among professionalism, organizationalprofessional conflict and various work outcomes for a sample of Certified Management Accountants. We assessed professionalism using Hall's Professionalism Scale, and tested the relationships among professionalism, organizational-professional conflict, organizational commitment, job satisfaction and turnover intentions using a structural equations model. The results indicate that two dimensions of professionalism (dedication to the profe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
96
1
7

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(110 citation statements)
references
References 44 publications
6
96
1
7
Order By: Relevance
“…Professionals and their employers may sometimes be strategically misaligned in terms of the goals, values and intent fostered and pursued by the professional and the organisation respectively (Bowen et al, 2007;Gamage, 2006;Shafer et al, 2002). There appears to be a distinctly different focus in the goals of the professional and that of the employing organisation as a result of differences in what society, stakeholders and the organisation regard as important determinants of their respective goals (Brooks, 2001).…”
Section: Organisation-professional Conflictmentioning
confidence: 99%
See 2 more Smart Citations
“…Professionals and their employers may sometimes be strategically misaligned in terms of the goals, values and intent fostered and pursued by the professional and the organisation respectively (Bowen et al, 2007;Gamage, 2006;Shafer et al, 2002). There appears to be a distinctly different focus in the goals of the professional and that of the employing organisation as a result of differences in what society, stakeholders and the organisation regard as important determinants of their respective goals (Brooks, 2001).…”
Section: Organisation-professional Conflictmentioning
confidence: 99%
“…Although various professions differ in terms of their subject matter, previous research on the nature and extent of OPC has shown that the predominant factors contributing to OPC are similar. Power tensions between the bureaucratic and hierarchical organisational structures and the need of professionals for autonomy and independence, seem to be the leading causes of conflict (Brandsen, 2009;Gamage, 2006;Gunz & Gunz, 2008;Shafer, 2002;Shafer, Park & Liao, 2002). There is, however, a paucity of research on the phenomenon of OPC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instrumen kepuasan kerja diadopsi dari Brayfield dan Rothe (1951) dalam Shafer (2002). Instrumen ini terdiri dari 7 item pertanyaan dengan 7 poin skala likert.…”
Section: Definisi Operasional Dan Pengukuran Variabelunclassified
“…Power in an organization comes from a multiplicity of sources, and the level of bureaucracy will determine the level of professional autonomy. Shafer et al (2002) suggest that organizational-professional conflict is found to contribute to dysfunctional work outcomes, such as a lower level of organizational commitment and higher turnover intentions. They further note that as professionals employed in organizations move up the hierarchy of an organization, they show greater concern for organizational values and less concern for professional values.…”
Section: Introductionmentioning
confidence: 99%